A survey of breeding waders on machair and other coastal grasslands in Counties Mayo and Galway - Suddaby, Dave; O'Brien, Irene; Breen, Dermot; Kelly, Séan (National Parks and Wildlife Service. Department of Culture, Heritage and the Gaeltacht, 2020)
Thirty-four coastal grassland sites in Counties Mayo and Galway were surveyed for breeding waders by National Parks and Wildlife Service staff in 2019. Sites were visited up to three times from April to June,following the same survey methods as in previous surveys at these sites. A total of 280 pairs were recorded, comprising seven species: Oyster catcher Haematopus ostralegus, Ringed Plover Charadrius hiaticula, Lapwing Vanellus vanellus, Dunlin Calidris alpina, Snipe Gallinago gallinago, Redshank Tringa totanus and Common Sandpiper Actitis hypoleucos, all of which are ground-nesting species.Twenty-four of the sites had been surveyed previously, in both 1996 and 2009. Comparisons with these surveys revealed total breeding wader population declines of 51% since 1996 and 62% since 2009. All breeding wader species have declined by 28% or more since 2009, with Dunlin showing the largest decline in numbers at 91%. Oystercatcher, Ringed Plover, Redshank and Common Sandpiper declined by 70% or more since 2009, whilst Snipe and Lapwing declined by 28% and 30% respectively since 2009. The recorded wader population declines were most evident on the offshore islands,where the total number of breeding pairs dropped by 65% since 1996 and 81% since 2009, with each breeding wader species declining by between 69% and 91% since 2009. During the 2009 survey, the Inishkea Islands Special Protection Area held the largest numbers of breeding waders at 377 pairs; however, only 68 pairs were recorded in 2019, a total decline of 82%. These declines are alarming and have likely primarily been driven by habitat change and increased predation pressure; both of which have been cited as root causes of global breeding wader population declines.Changes in the habitat structure were recorded at the surveyed grassland sites;for example,the coverage of tussocks, which many waders require for nesting, has decreased. This change is likely a result of increased grazing pressure in the recent decade; estimates of livestock grazing from this survey ...